Price determinants and classification of tactical pricing decisions in the cruise industry. Issue 2 (17th February 2021) - Espinet-Rius, Josep Maria; Gassiot-Melian, Ariadna; Rigall-I-Torrent, Ricard
ABSTRACT: Pricing strategies and tactics and itinerary design are some of the most important decisions faced by cruise companies in order to maximize their profits. This research aims both at analyzing factors that determine the price of a cruise package and at classifying cruise companies according to their pricing tactical decisions. In order to do so, we have gathered more than 84, 000 cruise prices corresponding to around 9, 200 departures for 2019, which belong to eight of the most important cruise companies. This paper combines two methodologies. On the one hand, hedonic regressions, which are commonly used in the tourism industry in order to identify factors affecting prices. On the other hand, cluster analysis, which allows us to classify cruise companies' pricing tactical decisions. The results obtained allow us to conclude that a few factors are able to explain more than 76% of the variance of the price: number of nights, type of cabin, month of departure, destination, cruise company and ship rating. Another relevant contribution of this paper is the definition of three clusters when analyzing tactical pricing decisions for cruise companies jointly and eight clusters when the analysis is carried out with ships.